Case reports: Central nervous system involvement in patients with newly diagnosed multiple myeloma - Liu, Jinghua; Shen, Jing; Liu, Daihong (Frontiers in Neurology, 2023)
Multiple myeloma with central nervous system involvement (CNS-MM) is rare, having a poor outcome and occurring in newly diagnosed or relapsed/refractory patients. The current report concerns 3 cases of newly diagnosed MM patients who presented with skull-derived plasmacytomas. Case 1 was a 54-year-old female patient with immunoglobulin D (IgD) subtype who developed extramedullary lesions from the sphenoid and occipital bones and the sphenoid sinus. Cases 2 and 3 had IgA subtype with left or bilateral frontal area lesions. Case 1 was treated with bortezomib, cyclophosphamide and dexamethasone (VCD) as the initial chemotherapy regimen and with bortezomib, lenalidomide, pegylated liposomal doxorubicin and dexamethasone (DVD-R) as the second line regimen. Whole-brain irradiation and intrathecal injection were given but the patient died within 9 months due to disease progression. Case 2 was treated with bortezomib, lenalidomide and dexamethasone (VRD) and received autologous hematopoietic stem cell transplantation (auto-HSCT) with a conditioning regimen of cyclophosphamide, etoposide and melphalan (CEM). Case 3 received DVD-R initially and auto-HSCT with a conditioning regimen of busulfan, cyclophosphamide, and etoposide (BuCyE). Cases 2 and 3 survived until the last follow-up more than three years later. Auto-HSCT with modified conditioning regimen as consolidation therapy improved the prognosis of CNS-MM.